KEUSAHAWANAN DAN USAHA KECIL DI PEDESAAN - Agus Sutanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
Since the 1970s, the growing interest on the development of small enterprises has been decorating the scene of government policy in developing countries as well as the international donor concern. The failure and cost of industrialization, the limitations of the agricultural sector, and the low capability of the formal sector in responding to the growing population are among the factors justifying this policy initiation. Another important factor is the intrinsic potential and prospect of small enterprises, despite their development problems. This research conducted on 4 villages within the Province of Yogyakarta Special Region and CentralJava is aimed at contributing to a rather comprehensive view on the profile of small enterprises and the profile of small entrepreneurs. A specific emphasis is given to rural entrepreneurship due to its crucial role in accelerating the development of small enterprises.